The Effectiveness of VBA-based File Management - Pribadi, Joni Dwi; Wijayanti, Rena Feri; Wardani, Tri Istining; Permanasari, Kartika Indah (Cita konsultindo, 2025)
File management is the process of organizing, storing, and manipulating digital files on a computer system. Several key aspects such as documents can be easily accessed, protected in terms of authenticity, and managed efficiently are criteria for good physical and digital file management. In addition, by implementing a good file management, archives can be easily and quickly retrieved again when needed, classified clearly, named consistently for easy tracking, protected from loss and damage, and maintained their authenticity for valid evidence. Not only that, the scalability of file management can also be developed according to future document growth, is adaptive to business needs, and sustainability maintained. This study aims to create and measure the effectiveness of a VBA-based File Management Application as a file mitigation effort in the Digital Era. This study uses action research and functional black box testing methods. The results of this study indicate that the VBA-based application created has met the criteria for good file management, namely easy to use, creates and stores documents securely, easy to trace back, reliably protected in terms of authenticity, and all its functions run as expected. This application is expected to be evaluated and monitored regularly during the implementation for further development.